Bioactivation of Polyaniline for Biomedical Applications and Metal Oxide Composites - Khalida Abbas Omran (Journal of Chemistry)
In this work, the oxidative chemical synthesis of polyaniline (PANI) in the presence of glutamic acid (GA) is presented, using ammonium persulfate (APS) as the oxidizing agent. Syntheses were performed by varying the molar ratio of aniline:amino acid:oxidant. The products of the different reactions were characterized by SEM, TEM, and FTIR techniques. It was observed that the molar ratio of aniline:amino acid:oxidant used in the synthesis determines the composition and conformation of the resulting polymer and its morphological and electrochemical properties. Composite hydrogels were prepared by incorporating the drug-loaded PANI nanofibers in situ through polymerization and cross-linking of acrylamide. TEM images of the cross-section of the hydrogel revealed the formation of a three-dimensional system of the polyaniline nanofibers maintained by the insulating matrix of the polyacrylamide hydrogel. The in vitro release of the drug from the hydrogels composed of polyacrylamide/polyaniline against buffer solutions at different pH and temperature was studied, using orbital agitation. Finally, considering the potential of hydrogels composed of polyacrylamide/polyaniline for the controlled release of drugs, a study was conducted to evaluate their cytotoxicity against normal mouse subcutaneous tissue cells.